Peningkatan Prestasi Belajar Matematika Melalui Model Pembelajaran Kooperatif Tipe Numbered Heads Together pada Siswa Kelas III SD Inpres Onekore 3 Kecamatan Ende Tengah Tahun Pelajaran 2017/2018 - Marselus Dawe (Ekspektasi: Jurnal Pendidikan Ekonomi, 2020)
The problem in this research is the low mathematics learning achievement achieved by students. Students who experienced learning completeness with KKM 65 reached 42,10% or as many as 8 people and students who had not completed learning were 57,89% or as many as 11 students. The data from the identification of problems showed that the average learning achievement obtained was 62,7. The highest and lowest scores achieved by students were 100 and 35 with a total of 4 students each. This study aims to improve teacher skills, students activities, and student mathematics learning achievement. The conclusion from the implementation of research using the NHT type cooperative learning model, namely the type of NHT cooperative learning model can improve teacher skills, student activities, and learning achievement.